Community Radio In Ireland: “Defeudalising” the Public Sphere? - Gaynor, Niamh; O’Brien, Anne (Javnost-The Public, 2011)
The growth in interest and research in community radio worldwide over the last few decades is a welcome development. While, as noted by Jankowski (2003), a first generation of research has been largely empirical in nature, describing and analysing the organisation and operation of stations in different contexts, more recently a second generation of work has begun to emerge which aims at grounding empirical studies within broader theoretical frameworks, most notably those relating to democracy and the public sphere. The specific components of the public sphere remain somewhat underdeveloped in these studies however. This article aims to contribute to this literature through an examination of community radio in Ireland within a framework drawn from evolving work of Habermas and associated deliberative, social and media theorists. The article, drawing on a detailed study of four community stations in Ireland, identifies elements of community radio which contribute towards a “defeudalisation” of the public sphere as well as highlighting challenges in this regard. Although situated within a specific context, with Irish community radio operating within a comparable regulatory environment to both that in Australia and the United Kingdom, the article draws lessons of specific interest to researchers and activists in these domains, as well as offering a framework of use to community radio researchers interested in examining the sector’s contribution to the re-animation of the public sphere more globally.